Strengthening Transformational Leadership of School Principals in Supporting Inclusive Education at Gunung Sekar 2 Elementary School - Nurhaliza, Indriyani; Putra , Safril Aditia; Sa’i, Mad (SANISKALA : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to strengthen the transformational leadership of school principals in supporting inclusive education at Gunung Sekar 2 Elementary School. The method used in this activity involves a descriptive qualitative approach through interviews, observations, and document analysis, which were systematically conducted and presented. The implementation of this program produced three main outcomes: first, it introduced and reinforced the concept of transformational leadership among school principals; second, it supported the development of leadership systems related to inclusive education practices at SDN Gunung Sekar 2; and third, it identified the supporting and inhibiting factors faced by school principals in formulating and implementing inclusive education policies. The results show that the principal of SDN Gunung Sekar 2 has taken appropriate steps by engaging parents and school staff in creating and sustaining an inclusive school environment. Furthermore, the principal has successfully applied values of empathy and mutual respect, which foster a positive and supportive atmosphere for all students to learn and grow.